Effectiveness of Long Bean Leaf Green Noodles in Enhancing Prolactin Levels in Breastfeeding Mothers - Nurhidayah, Siti; E.U Djami, Moudy; Estiyanti, Erni; Ayunita Sabilla, Wulan (Indonesian Journal of Obstetrics and Gynecology, 2025)
Abstract Breastfeeding plays an important role in meeting the nutritional needs of infants and is useful in preventing malnutrition in children. However, insufficient breast milk is one of the obstacles in this process. Interventions that can be done to increase breast milk can be done pharmacologically using Domperidone. On the other hand, the drug can trigger side effects, then the use of herbs is recommended. Long bean leaves (Vigna sinensis L.) are plants that are rich in nutrients and can stimulate prolactin through the phytocemichal contents(1)(2)(3). Objectives: The aims of the research to be carried out is to formulate and analyze the effectiveness of Green Noodles based on long bean leaves (Vigna sinensis L.) to help increase prolactin of breasfeed mother. Methods: The research method used is a quasi-experimental with a Nonrandomized Control Group Pretest-Postest Design consisting of an experimental group (given green noodles) and a control group (given plain Noodles). The intervention was carried out for 14 days by giving green noodles 2 times a day for 14 days. Results: Green noodles contain 4 times higher levels of polyphenols than white noodles with amounts of 384.55 mg/kg and 85.39 mg/kg respectively. Based on the results of pre and post interventions in both intervention and control groups, it was found that breastfeeding mothers who consumed Green Noodles experienced an increase in prolactin levels (p value 0.004) and mothers who consumed White Noodles did not experience a significant increase in prolactin levels (p value 0.283). Conclusion: Green noodles is rich in polyphenols which can help increasing prolactin hormone on breastfeed mother. Keywords: Breastmilk; Long Bean Leaves; Breastfeeding; Prolactin; Vigna sinensis L.